The linear relationship between compressive strength and ultrasonic velocity in castable refractories - Yaman, C; Abkan, T; Akdogan, A (TRANS TECH PUBLICATIONS LTD, 2004)
In this experimental work, castable refractory has been used. In pressing the water percent was in the range of 7.5-9.5 % weight, and the seven cylindrical specimens for each mixture have been pressed under 4000 N/cm(2) into a steel mould. In casting the water percent was in the range of 10-12 % weight. After mixing castable with water, the specimens, which contain more than 9.5 % water, have been casted to 40 x 40 x 40 mm(3) into a steel mold by vibrating.
Keywords: ultrasonic velocity; castable refractory; refractory concrete; SINTERED CERAMICS; GREEN; ALUMINA; Materials Science